Decoding the Neurocognitive Consequences: A Comprehensive Analysis of Smoking and Alcohol Consumption on Cognitive Function Across the Lifespan - Amanda Konoralma, Rahel; Wilson Setiawan, Andreas; Anggraini, Tyas; Arsita, Cynthia; Hikmah, Abidatul; Maretha Krisopras, Hawila; Nisa Belladiena, Alfiena (Health Science UDINUS, 2024)
The smoking rate continues to rise yearly, with significant increasesobserved among men across children, adolescents, and adults. Alcoholconsumption caused 2.6 million deaths in 2019, with 2 million casesamong men and 0.6 million among women. This study aimed to evaluatethe influence of smoking status and alcohol consumption on cognitivefunction. Cognitive impairments (difficulties in thinking andunderstanding) are increasing health concerns, particularly in developingcountries. This research was an analytic observational design with across-sectional approach, utilizing secondary data from 3,000 samplescovering various health and lifestyle factors. The synthetic dataset mimicsreal-world conditions, offering a controlled environment to examineassociations and minimize confounding biases—statistical analysis to assess the relationship and differences in cognitive function based onsmoking status and alcohol consumption. The results showed a significantcorrelation between smoking habits and cognitive function, with nonsmokers exhibiting better cognitive performance compared to active andformer smokers. Alcohol consumption did not demonstrate significant differences in cognitive function, suggesting that factors such as consumption patterns and quantity may have a more substantial impact.Public health campaigns should leverage these insights to promotesmoking cessation and address broader lifestyle factors influencingcognitive function.